Review of Methods for Reducing Circulating Currents in Parallel Connected Modular Inverters - Choi, Hye Won; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2023)
Parallel-connected modular inverters are widely used in high-power applications to increase the power capacity of the system. These modular inverters offer convenient maintenance and an adjustable power rating. However, when the inverters share a common DC source and AC bus, a circulating current is generated, which causes output current distortion and system power losses. These harmonic components of circulating current influence the inverter life cycle, and it can limit the power rating of the total parallel-connected inverter. This study analyzes the circulating current according to its causes and reviews the reduction methods. The reduction methods for modular inverters are compared in terms of efficiency, performance, and reliability. The possible approaches for circulating current reduction are categorized into three groups–hardware, control, and modulation. Each reduction method is discussed according to the category. Finally, the performance of the methods is analyzed, and their advantages, disadvantages, and prominent features are highlighted.
Keywords: Circulating current; High frequency HF; High-frequency circulating current; Low-frequency circulating current; Lower frequencies; Modulars; Parallel inverter; Power conversion systems; Reduction method; High-frequency circulating current; Low-frequency circulating current; Parallel inverters; Power conversion system; Reduction method; Reliability